Pengaruh Atraksi Wisata Dan Fasilitas Terhadap Keputusan Berkunjung Kembali Di Pantai Tongaci Sungailiat - Sofiani, Sofiani; Eugenia , Valeri (Sadar Wisata: Jurnal Pariwisata, 2023)
Pantai Tongaci Sungailiat is a tourist destination in The Province of Bangka Belitung which has various and adequate attraction and facility. However, the number of tourist visits in recent times has been decreased. This research was conducted with the aim of seeing and analyzing the influence of tourist attraction and facility on revisit decision at Pantai Tongaci Sungailiat. The research method that will be used in this research is a quantitative method with total sample of 397 respondents. Data will be collected using questionnaires, observations and interviews. The test method that will be using reliability and validity tests, normality test, heteroscedasticity test, multicollinearity test, multiple linear regression test, coefficient of determination test, partial test / t test, simultaneous test / f test and mean test. The results of the tests indicate that tourist attractions and facilities both partially and simultaneously have a significant and positive influence on revisit decision at Pantai Tongaci Sungailiat and Facility is a variable that is more dominant influence. Simultaneously, the influence given is 28,1%. The influence categorized as low category. Pantai Tongaci Sungailiat needs to pay attention to tourist attraction and existing facilities, also add some new inovations related to tourist attractions and facilities to increase tourist revisit decision to Pantai Tongaci Sungailiat.